The Impact of the Earthquake in Racha on the Enguri Arch Dam and the Adjacent Area - Kiria, Jemal K.; Tsaguria, Temur A.; Sakvarelidze, Evgeni A.; Dovgali, Nadezhda D.; Davitashvili, Lali A.; Kutelia, Guram A. (Journals of Georgian Geophysical Society, 2024)
As is well known, the Enguri Arch Dam, 271.5 meters high, was constructed on the Enguri River in the 1970s. It is built in a seismically active region with a complex geological structure. The Enguri Dam’s foundation crosses a branch of the Ingirishi fault, on which geophysical monitoring (using a deformograph) is conducted. The fault’s edges move with the variation of the water level in the dam reservoir. Strong earthquakes can also cause displacement of the fault’s edges. This was the basis for conducting parallel geological, geophysical, geodetic, and other types of monitoring during the design and construction of the dam, some of which continue to this day.